92.1k views
0 votes
Proved that
V = u+at


2 Answers

5 votes

Answer:

Acceleration = v-u/t when we flip -u and t to right hand side

then -u changes to plus and denominator t changes to numerator

then then this equations becomes v=u+at

Step-by-step explanation:

User Skydv
by
4.3k points
0 votes

Answer:


\sf Proof \ below

Step-by-step explanation:

We know that acceleration is change in velocity over time.


\sf a=(\triangle v)/(t)


\sf a=(v-u)/(t)

v is the final velocity and u is the initial velocity.

Solve for v.

Multiply both sides by t.


\sf at=v-u

Add u to both sides.


\sf at + u=v

User Vikrant Kashyap
by
4.7k points